2018
DOI: 10.1007/s00259-018-3969-4
|View full text |Cite|
|
Sign up to set email alerts
|

Biological tumour volumes of gliomas in early and standard 20–40 min 18F-FET PET images differ according to IDH mutation status

Abstract: BTVs delineated in early and standard summation images differed significantly in more than half of gliomas. While the standard summation images seem appropriate for delineation of LGG as well as IDH-mutant gliomas, a remarkably high percentage of HGG and, particularly, IDH-wildtype gliomas were depicted with significantly larger volumes in early summation images. This finding might be of interest for optimization of treatment planning (e.g. radiotherapy) in accordance with the individual IDH mutation status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…Recently,11C-MET and18F-FET PET were proved to allow a better delineation of tumor margins and improve targeting of biopsy and radiotherapy, suggesting the application of biological tumor volume defined by SUV value in radiotherapy of gliomas. 47,48 However, a meta-analysis comparing the diagnostic ACC of different imaging technique to delineate diffuse gliomas reported that for LGGs, the area under the hsROC curve was higher for MRS (0.781) than T2/FLAIR (0.774), followed by PET-MET (0.668) and PET-FET (0.649). The false-positive rate was lower in MRS (36.1%) than in PET-FET (38.5%); the true-positive rate was highest for MRS (87.3%), followed by T2/FLAIR (65.8%) and PET-FET (60%).…”
Section: Discussionmentioning
confidence: 99%
“…Recently,11C-MET and18F-FET PET were proved to allow a better delineation of tumor margins and improve targeting of biopsy and radiotherapy, suggesting the application of biological tumor volume defined by SUV value in radiotherapy of gliomas. 47,48 However, a meta-analysis comparing the diagnostic ACC of different imaging technique to delineate diffuse gliomas reported that for LGGs, the area under the hsROC curve was higher for MRS (0.781) than T2/FLAIR (0.774), followed by PET-MET (0.668) and PET-FET (0.649). The false-positive rate was lower in MRS (36.1%) than in PET-FET (38.5%); the true-positive rate was highest for MRS (87.3%), followed by T2/FLAIR (65.8%) and PET-FET (60%).…”
Section: Discussionmentioning
confidence: 99%
“…The biological tumor volume of early glioma differs from the standard 20-40 min FDG-PET to determine IDH status [24]. Moreover, several studies revealed an association between the FDG uptake and the status of IDH mutation or the prognosis of glioma [24,25], as SUVmax or different ratio based on SUV showed its diagnostic value.…”
Section: Introductionmentioning
confidence: 99%
“…MET-PET/MRI has been reported to predict the IDH mutation of gliomas, by calculating the maximum tumor-brain ratio of MET uptake, and the receiver operating characteristic (ROC) analysis showed high AUC of 0.79 [23]. The biological tumor volume of early glioma differs from the standard 20-40 min FDG-PET to determine IDH status [24]. Moreover, several studies revealed an association between the FDG uptake and the status of IDH mutation or the prognosis of glioma [24,25], as SUVmax or different ratio based on SUV showed its diagnostic value.…”
Section: Introductionmentioning
confidence: 99%
“…Early static FET-PET scans have a higher accuracy for glioma grading than the standard 20-40 min scans ( 15 ). Whereas, PET 20–40 min post-injection seems appropriate for delineation of low-grade gliomas as well as IDH-mutant gliomas, high-grade gliomas, and some IDH wildtype gliomas seem to have larger volumes in early images ( 16 ). Dual time-point FET-PET is a promising compromise that might improve glioma grading and definition of tumor borders using two static images early (5–15 min post-injection) and late (50–80 min post-injection) after radiotracer injection ( 17 , 18 ).…”
Section: Introductionmentioning
confidence: 99%